De la place de la théorie de la valeur et de la monnaie dans la théorie de la régulation : critique et synthèse - Matthieu Montalban (Revue de la Régulation)
Marxists and régulationnists are opposed on the usefulness value theory, especially labour theory of value. We show how régulationnists, that at the beginning were defending labour value theory, have substituated it to a theory of money. We show that the main problem for marxism is the socialization of private labour by market and the fact that Labour Theory of Value has for only object the demonstration of exploitation. After having shown the interest of research program on money, we emphazise some limits of such position, because Orléan and Lordon are developing in fact a theory social construction of use value, especially the lack of pricing theory. We also show that the theory of exploitation and the question of new wealth indicators needs a value theory.